Cryopreservation of Mammalian Gametes and Embryos Methods and Protocols - Nagy, Zsolt Peter; Varghese, Alex C.; Agarwal, Ashok (Methods in Molecular Biology, 2017)
This volume provides a comprehensive and technical presentation of numerous aspects of reproductive cell tissue cryopreservation, and presents readers with current procedures and detailed discussions of novel techniques and the latest innovations. The chapters in this book are divided into five parts and cover subjects such as: immature oocyte cryopreservation, human sperm vitrification and slow-freezing, directional freezing of ovarian tissue, automated vitrification systems, and detailed protocols on popular and commercially available cryopreservation/vitrification systems. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Cutting-edge and practical, Cryopreservation of Mammalian Gametes and Embryos: Methods and Protocols includes chapters written by leading experts in the field and is a valuable resource for anyone interested in the field of cryopreservation.